Neural Networks in Modelling Maintenance Unit Load Status - Vojvoda, Anđelko; Gold, Hrvoje (Promet - Traffic&Transportation, 2002)
This paper deals with a way of applying a neural networkfor describing se1vice station load in a maintenance unit. Dataacquired by measuring the workload of single stations in amaintenance unit were used in the process of training the neuralnetwork in order to create a model of the obse1ved system.The model developed in this way enables us to make more accuratepredictions over critical overload. Modelling was realisedby developing and using m-functions of the Matlab software.